Environmental initiatives of SMEs in Malaysia: an investigation of reporting practice and motivations / Nik Zam Nik Wan - Nik Wan, Nik Zam (2016)
SMEs are considered as the backbone of most economic growth worldwide including Malaysia but their existence and importance as individual are frequently under estimated. SME’s individual environmental impacts seem to appear at a minimum level but environmental cases reported otherwise. Even though they should be equally accountable, little is known about SMEs’ initiatives in preserving the environment. Inspired by the above, this study decided to explore Malaysian SMEs’ involvement in environmental initiatives including environmental reporting. The motivations for environmental initiatives of SMEs in Malaysia are investigated to provide opportunities to encourage and to educate more SMEs to implement the environmental initiatives and communicate their environmental information. This study used qualitative research methodology employing grounded theory approach. The data collection process included semi-structure interviews, content analysis of documents and observations and focused only on SMEs that are registered as members of FMM. Through interviews, observations and content analysis this study revealed that the SMEs did implement some environmental initiatives. Despite being said to be smaller in nature findings of this study indicated that Malaysian SMEs also demonstrated their responsibility towards the environment. These SMEs not only complied with the related environmental rules and regulations but they also committed their limited financial resources to implement several environmental initiatives. Among the non-mandatory initiatives implemented are environmental management system, waste management, energy conservations, tree planting and creating environmental awareness. It was identified that the SMEs did have environmental reporting as part of their environmental initiatives. They communicated to their stakeholders the companies’ environmental policies and objectives, their environmental friendly practices and the environmental initiatives implemented. However, it was also identified that the information was provided more on ad hoc basis rather than systematically and periodically and mostly did not convey the complete information of actual environmental initiatives implemented. Thoroughly, this study discovered the key motivating factors for environmental initiatives amongst SMEs by reviewing the ‘who’ could motivate from the lenses of the Stakeholder theory which give rise to a ‘stakeholder-driven factor’. Meanwhile, the Institutional theory is utilised to justify as to ‘how’ the SMEs are influenced to engage in environmental initiatives and it give rise to ‘institutional-drive’. It was identified that regulators, customers, the environment through the nature of the business and owners-managers are the factors that could motivate the SMEs to implement the environmental initiatives. Without doubt, the findings of this study support the Stakeholder theory. The theory is further enhanced by providing thorough and in-depth explanation of the relation between the SMEs and its stakeholders. This has given rise to the discovery that not all the SMEs’ customers will become the motivating factors for them. There are only some categories of customers that can act as motivating factors meanwhile others cannot. SMEs’ Implementation of Environmental Initiatives Index is developed from the findings and can be utilised to identify the possibility for an individual SME to engage in environmental initiatives. Since this study has revealed that SMEs did implement environmental initiatives and practice environmental reporting, they should be motivated to present the information to the public. Environmental reporting could act as evaluation tools to assess the SMEs equally accountability towards the environment.